The Dynamics of Mental Block as a Barrier to Student Learning from the Perspective of Behaviorist Theory in the Classroom Learning Process - Hasanatun Nadiyah; Nazlah Hidayati (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
This research discusses mental block as one of the learning barriers experienced by students of class XII B at MA An-Najah I Karduluk Sumenep. Mental block is characterized by passive behavior in learning activities, low self-confidence, fear of making mistakes, and a tendency to delay or avoid assignments. The purpose of this study is to analyze the forms of mental block and the factors influencing it from a behavioristic perspective. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The informants consisted of guidance and counseling teachers, homeroom teachers, the principal, the vice principal for student affairs, and students who showed symptoms of mental block. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that mental block appeared in the form of passive classroom behavior, lack of self-confidence, fear of answering questions, and procrastination in completing assignments. The factors influencing this condition included academic pressure, unpleasant learning experiences, and the lack of positive reinforcement from the learning environment. From a behavioristic perspective, mental block is understood as a behavioral response formed by repeated environmental stimuli during the learning process. This study highlights the importance of positive reinforcement in reducing students’ learning barriers and developing more active and confident learning behaviors.